The internal supervisory activities in the English department of St. Stephen's High School and their conceptual bases - Cudiamat, Dolores de los Reyes 1928- (s.n.], 1970)
This study is about the conceptualization and analysis of the internal supervisory activities in the English Department of the St. Stephen's High School. The conceptualization and analysis led to the following conclusions: (1) that the internal supervisory activities in the High School Department of the school are of the type and kind accepted by education authorities on the subject; and (2) that the activities are solidly based on accepted concepts and principles either in education or in other disciplines like Sociology and Anthropology.